Acute Uterine Inversion: Case Series from Paropakar Maternity and Women’s Hospital - Upadhyaya, Indira; Chaudhary, P (Nepal Journal of Obstetrics and Gynaecology, 2013)
Acute puerperial uterine inversion is a rare life threatening obstetric emergency, in which the uterine fundus collapses into and out of the uterine cavity. Although precise cause is unknown, it is postulated to be caused by the mismanagement of the third stage of labour. The duration of time elapsed from moment of diagnosis to that of correction, along with rapid resuscitation measures are of utmost importance in its prognosis. Principle of treatment includes resuscitation followed by manual reduction of inversion uterus. Surgical procedure may be needed if reinversion is impossible. Reporting here are series of cases with acute inversion of uterus at third stage of labour followed by a short review of the literature. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 46-49 DOI: http://dx.doi.org/10.3126/njog.v8i1.8865